Strategi Peningkatan Nilai Tambah Komoditi Usaha Tani Sagu Di Kecamatan Belopa Kabupaten Luwu - Kartina Kartina; Nurdiana Nurdiana; Muhammad Hasan; Tuti Supatminingsih; M. Ihsan Said Ahmad (Economic Education and Entrepreneurship Journal, 2021)
This study aims to analyze the potential development of sago commodity in Belopa District, Luwu Regency and determine strategies to increase its added value. This study uses a qualitative approach that is descriptive analysis. Data collection techniques through observation, interviews and documentation.Research subjects were determined based on the criteria determined by the researcher, which consisted of sago farmers as key informants, home industries processing sago-based food, sago traders and local government as additional informants. The data analysis technique used is SWOT analysis. The results showed that the effort to increase the added value of the sago farming commodity in Belopa District, Luwu Regency is very dependent on the internal and external conditions of the farming business from upstream to downstream as the object to be developed. The results of the calculation of the combined strategy planning obtained that the highest score is the SO strategy, which is 25.6. So the set of strategies that should be chosen is the SO strategy which includes two alternative strategies, namely improving the quality of human resources to support the diversification of sago processed products and utilizing the availability of sago plants and raw materials for sago. adding variants (varieties) of processed sago products in order to support the culture of buying souvenirs.